Evidence basis for using dexmedetomidine to enhance the quality of paravertebral block: A systematic review and meta-analysis of randomized controlled trials - Tang, Rong; Liu, Yu-Qian; Zhong, Hai-Lian; Wu, Fang; Gao, Shi-Xiong; Liu, Wei; Lu, Wen-Sheng; Wang, Ying-Bin (Frontiers in Pharmacology, 2022)
Background. Dexmedetomidine has been proposed as an adjuvant to local anesthesia (LA) to prolong peripheral nerve block time. However, results from our previous meta-analysis were not sufficient to support its use in paravertebral block (PVB). Therefore, we conducted an updated meta-analysis to evaluate the efficacy of dexmedetomidine combined with LA in PVB. Methods. An electronic database search was conducted from inception date to April 2022. Randomized controlled trials (RCTs) investigating the addition of dexmedetomidine to LA compared with LA alone for PVB in adult patients were included. Postoperative pain scores, analgesic consumption, and dexmedetomidine-related side-effects were analyzed using random- effects modeling. Results. We identified 11 trials (641 patients), and found that the application of dexmedetomidine as a PVB adjunct reduced the postoperative pain severity of patients at 6 h, 12 h and 24 h after surgery compared with the control group. Expressed as MD [95%CI], the results were -0.83 [-1.17, -0.49], (P < 0.00001) for 6h, -0.87 [-1.27, -0.48], (P < 0.00001) for 12h, -1.03 [-1.57, -0.49], (P =0.0002) for 24h. Furthermore, dexmedetomidine prolonged the duration of analgesia by at least 171.10min [97.70, 244.49], (P < 0.00001), and reduced postoperative oral morphine consumption by 18.01mg [-22.10, 13.92], (P < 0.00001). In contrast, dexmedetomidine increased the odds of hypotension by an OR of 2.13 [0.98, 4.60], (P =0.06), it also increased the odds of bradycardia by an OR of 2.70 [0.82, 8.93], (P =0.10). There were no significant statistically differences in hemodynamic complications between the two groups. No patients experienced any neurologic sequelae. Evidence quality for duration of analgesia was high according to the GRADE system. Conclusions. New evidence now indicates that perineural dexmedetomidine improves PVB onset, quality, and analgesia. However, these benefits should be weighed against increased risks of transient bradycardia and hypotension.